Coverage of nutrition and health interventions in India: Insights from the National Family Health Surveys - Christopher, Anita; Gune, Soyra; Avula, Rasmi; Nguyen, Phuong Hong; Menon, Purnima; Singh, S. K.; Dwivedi, L. K.; Pedgaonkar, Sarang; Puri, Parul; Chauhan, Alka (International Food Policy Research Institute, 2023)
Nutrition-specific interventions are aimed at improving the food, health, and care environment for women and children during the first 1000 days. These interventions span pregnancy, postnatal, and early childhood periods and include food and micronutrient supplementation, nutrition education and/or counselling, growth monitoring and promotion, as well as routine immunization, deworming, and care during illness. At 90% coverage, these interventions can contribute to 20% reduction in stunting and 61% reduction in severe wasting. India’s policy framework for health and nutrition is robust and includes most evidence-based nutrition and health interventions. Two large-scale national program platforms – the Integrated Child Development Services and the National Health Mission – together deliver these interventions across the country. India’s efforts at scaling up nutrition interventions are now also bolstered by the National Nutrition Mission. This Data Note describes the coverage of key nutrition and health interventions for which data are available in the National Family Health Surveys for 2015-2016 and 2019-2021. To examine coverage of interventions, indicators were created based on global definitions and making adaptations to Indian policy context where necessary. Data on women of reproductive age (15-49 years) with a child below five years of age from the most recent birth was used to compute these indicators. Indicator definitions are provided in Annex 1 of this Note.